The Relationship Pattern Between Political Parties, Candidate Figures, and Constituents in the Regional Head Election Contest in Makassar City - Imam Mukti; Arlin Adam; Syamsidah, Syamsidah; Syamsu A. Kamaruddin (Journal of Social and Humanities, 2025)
This study aims to describe the pattern of relations between political parties, figures and constituents in the regional head elections in Makassar City, to elaborate on the political communication strategies of figures in building patterns of relations with political parties and constituents in the regional head elections in Makassar City, and to find relevant theoretical solutions in providing political education for constituents and increasing active participation of constituents in the regional head elections in Makassar City. The method used is a Qualitative approach, with the research paradigm used, namely Post Positivistic. The results of the study indicate that the relationship between political parties and candidate figures is transactional, where material interests and power are the main binders. This relationship often exploits and dominates constituents, prioritizing symbolic politics and the use of money as the main tool in building relationships.